The preceramic period in southeast asia-issue problem and future direction. - Majid, Zuraina

(untitled)
This Paper discusses the outstanding issues in Southeast Asian archaeology during the preceramic period.Archaelogical research that has been done in this region of sites from the late upper Pleistocene.